ANALISIS DETERMINAN TRANSFER PEMERINTAH PUSAT BERUPA DANA ALOKASI KHUSUS PADA KABUPATEN/KOTA DI PROVINSI MALUKU - Abdul Azis Laitupa (Jurnal Cita Ekonomika, 2017)
Implementation of regional autonomy in Indonesia provides the right and authority for the government to explore its potential and improve its financial performance to meet the needs and services. This study was to observe the effect of the independent variable is economic growth that is proxied by the PDRB, the original income (PAD) and the number of population on the dependent variable is the Special Allocation Fund (DAK) in Ambon City, Central Maluku and Southeast Maluku regency in Maluku province from the year 2003-2013. the method used in this research is panel data regression. The results showed that there is significant influence of the independent variable, economic growth is proxied by the PDRB, revenue (PAD) and the number of population on the amount of central government assistance in the form of general allocation funds in Ambon City, Central Maluku and Southeast Maluku District in the Province Maluku.